Reassessing State Responsibility for Indigenous Rights to Natural Resources Based on Justice Principle - Soelistyowati, Soelistyowati (Faculty of Law, Jambi University, 2024)
Indigenous peoples' existence is intrinsically linked to their customary rights, with significant disputes arising over the formal recognition of these rights. However, conditional or partial legal recognition frequently disadvantages indigenous communities. The state has a responsibility to uphold the rights of indigenous peoples, necessitating regulations that effectively safeguard their land rights. This article examines the recognition and fulfilment of indigenous peoples’ rights to natural resources through legal analysis, conceptual frameworks, and case studies. The findings indicate that since 1998, there has been a governmental intent to formally recognize indigenous rights to natural resources, as reflected in various laws and regulations. However, the implementation of these rights has been challenging due to ambiguities in the 1945 Constitution and the related regulations. Effective fulfilment of Indigenous land rights must adhere to key principles, including recognition of jurisdictional areas, the right to self-determination, Indigenous consent, community involvement, and the provision of fair compensation